The Arvon book of life writing : writing biography, autobiography and memoir - Cline, Sally (Methuen Drama, 2010)
Fascinating, wide-ranging, hugely knowledgeable - an indispensable guide and a beguiling education William Boyd Packed with insights and advice - just the inspiration to start writing! Jenny Uglow Everyone has a story This book shows how the best writers tell them, and offers advice on how to tell them yourself. Biographers Sally Cline and Carole Angier teach life writing - an area of creative writing that is exploding in popularity - at the world-famous Arvon Foundation. They have distilled the essence of their popular course on memoir, autobiography and biography into this wide-ranging bo.